Capital market returns and inflation nexus in Croatia: Wavelet coherence analysis - Mile Bošnjak; Ivan Novak; Maja Bašić (Business Systems Research (BSR), 2021)
Background: Hedging against inflation assumes instruments such as gold, stocks, fixed income securities, and real estate. There still exists a lack of appropriate strategy to hedge against inflation. Objectives: This paper examines the possibilities for hedging against inflation in Croatia offered by the Zagreb Stock Exchange indices. Methods/Approach: Based on monthly data from January 2000 to September 2019 and using a wavelet coherence approach, this paper brings the results across time and frequency domains. Results: Empirical results suggest that inflation was a leading variable in a statistically significant positive correlation between the inflation rate and Crobex returns in 2007-2011. The relationship between Crobex10, Crobis, and Crobistr returns on one side, and the inflation rate on the other side has statistically significant correlations only in specific and different periods, in which respective returns are a leading variable. Conclusions: The results imply that hedging against inflation is rather problematic under current Croatian capital markets conditions. Zagreb Stock Exchange indices could serve as a hedge against inflation for some periods but not during the whole observation period.
Keywords: E31; E37; G11; 330; inflation; hedging; wavelet analysis; stock market index